Fireproof and flame-retardant integrated coating and preparation method thereof
By using ground polymers prepared from coal gangue and fly ash solid waste as binder, combined with organic modification and inorganic fillers, the ceramic layer insulation ability and flame retardant performance of fire-retardant coatings are improved, and the existing technology is solved The problems of high cost and poor environmental performance have achieved low-cost, environmentally friendly high-performance fire-retardant coatings.
Patent Information
- Application Number
- CN202411796776.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-14
AI Technical Summary
The fire resistance mechanism of existing geological polymer fire-resistance coatings depends on the addition of a large amount of inorganic fillers with good thermal insulation, resulting in high costs and underutilization of solid waste, and further improvement of fire resistance and environmental protection performance.
The geopolymer prepared by coal gangue and fly ash solid waste is used as the coating binder, and the thermal insulation ability and flame retardant performance of the coating are improved by the combination of organically modified polymer binder and inorganic filler.
It realizes a low-cost, environmentally friendly, non-expanded fire-retardant integrated coating with ceramic layer heat insulation ability, improves the fire resistance level and fire resistance of steel structures, and solves the energy of existing cement-based and organic adhesive coatings. High consumption, unenvironmental protection, easy aging, low fire resistance and other problems.
Smart Images

Figure CN119432228A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fireproof and flame retardant coatings, and in particular to a fireproof and flame retardant integrated coating and a preparation method thereof. Background Art
[0002] Steel structure buildings have the advantages of light weight, high strength, flexible construction, recyclability, good earthquake resistance, etc., and are widely used in modern buildings. However, the thermal conductivity and thermal expansion coefficient of steel materials are very high, and its mechanical properties are inversely proportional to temperature. Therefore, the yield stress of steel will drop significantly in a fire, causing plastic deformation, loss of load capacity, and then the building collapse accident. Therefore, the fire resistance level of steel structures must be improved. At present, the method of coating fire retardant coatings on the surface of steel structures has been widely adopted due to its convenient construction, simple operation, and significant improvement in the fire resistance of steel structures.
[0003] Steel structure fire retardant coatings can be divided into two types according to the fire retardant mechanism: expansion type and non-expansion type. Among them, non-expansion type fire retardant coatings are generally composed of inorganic gelling materials as film-forming materials, fire retardant fillers and appropriate additives. Its fire retardant mechanism mainly forms an inorganic barrier layer between the substrate and the fire source through the flame retardancy and low thermal conductivity of the coating itself. Unlike expansion type coatings, it has the advantages of anti-aging, no expansion when exposed to water, excellent thermal insulation performance, high fire resistance limit, etc. It will not produce toxic smoke when exposed to high temperatures, meets the environmental protection requirements of "economy, efficiency, ecology, and energy", and is conducive to reducing casualties during fires and rescue processes. In addition, non-expansion type coatings can be sprayed in a simple and flexible manner, which significantly shortens the construction time, thereby reducing construction and maintenance costs.
[0004] At present, geopolymer, as a new inorganic gelling material with the greatest potential to replace cement, has been widely used in the field of fire-retardant coatings to replace cement-based materials. For example, Ai Tao, Zhao Peng and others (patent publication number CN103232197B) used silica fume, kaolin, calcium-based bentonite, calcium oxide, sodium carbonate, sodium chloride, sodium sulfate, and low-calcium fly ash to prepare geopolymer binder in advance, and then added expanded perlite, expanded vermiculite, brucite fiber, sepiolite, hydroxymethyl cellulose, and fatty alcohol sulfonate air entraining agent to the geopolymer to prepare a low-cost, long-fire-resistant, and high-bonding strength tunnel fire-retardant coating. Ma Wenqi and others (CN117264445A) used metakaolin-based polymer, pure styrene-acrylic emulsion, composite phosphate, titanium dioxide, and water to synthesize a metakaolin-based polymer interior wall fire-retardant coating, which has good bonding properties and fire-resistant and heat-insulating properties. However, the improvement of the fireproof mechanism of the above-mentioned geopolymer fire retardant coatings is achieved by adding a large amount of inorganic fillers with good thermal insulation as a thermal insulation barrier, the cost is still too high, and solid waste has not been widely used. Therefore, it is necessary to further improve the fireproof mechanism of geopolymer fire retardant coatings to obtain a low-cost, environmentally friendly, non-expansive fire-retardant integrated coating with ceramic layer thermal insulation capacity. Summary of the invention
[0005] The main purpose of the present invention is to provide a fire-retardant integrated coating and a preparation method thereof. The coating matrix uses a geopolymer prepared from coal gangue and fly ash solid waste as raw materials instead of cement or organic glue as a coating binder, thereby ensuring bonding strength while being environmentally friendly.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A fire-retardant integrated coating, comprising the following components in parts by weight:
[0008] 157-290 parts of organic modified polymer binder, 10-18 parts of inorganic filler, 22-54 parts of flame retardant flux, 5-21 parts of plasticizer;
[0009] in,
[0010] The organic modified geopolymer binder comprises 40-70 parts of fly ash, 20-40 parts of calcined coal gangue powder, 10-30 parts of metakaolin; 60-100 parts of alkali activator, 25-45 parts of organic silicone resin, 2-4 parts of silane coupling agent, and 0.2-2 parts of defoaming agent;
[0011] The inorganic filler comprises 4 to 6 parts of mica powder, 3 to 5 parts of zirconium oxide powder, and 3 to 7 parts of sepiolite powder;
[0012] The flame retardant flux comprises 10 to 30 parts of low melting point glass powder, 8 to 16 parts of zinc borate, and 4 to 8 parts of sodium polyphosphate;
[0013] The plasticizer comprises 2 to 10 parts of montmorillonite, 1 to 5 parts of brucite and 2 to 6 parts of hydrotalcite.
[0014] Specifically, the utilization rate of coal gangue and fly ash of the fire-retardant integrated coating can reach 60-80%; by further improving the coal gangue geopolymer fire-retardant coating, the high-temperature heat insulation and fire-retardant performance of the geopolymer can be improved in a low-cost manner. Due to the further improvement of the fire-retardant mechanism of the geopolymer fire-retardant coating, a low-cost, environmentally friendly, non-expansive fire-retardant integrated coating with ceramic layer heat insulation capacity is obtained.
[0015] The invention discloses an environmentally friendly ceramic organic-inorganic polymer hybrid geopolymer-based steel structure fire retardant coating. Compared with cement-based and gypsum-based coatings, geopolymer-based coatings have better high-temperature stability and lower thermal conductivity. Geopolymers can release a large amount of water molecules under high temperature conditions, reduce the ambient temperature and dilute the surrounding combustible gas, and have gas phase flame retardant and heat insulation effects. However, geopolymers cannot avoid cracking under high temperature conditions, so organically modifying geopolymers using silicone resins and silane coupling agents, and combining the characteristics that geopolymers can be transformed into ceramic phases at high temperatures, using organic modified geopolymers as binders to prepare fire retardant coatings is a choice that achieves twice the result with half the effort. Sepiolite, mica powder and zirconium oxide ceramic powder serve as inorganic inert fillers to enhance the heat insulation effect of pore coordination sheets. Flame retardant fluxing agents can melt the surface of geopolymer fire retardant coatings, absorb a large amount of surface heat, and fill the microcracks that appear in time.
[0016] Preferably, the alkaline activator comprises a sodium silicate water glass solution and a sodium hydroxide solution in a mass ratio of 1.1 to 1.4:1, the Baume degree of the sodium silicate water glass solution is 38.5 to 50 Be, the concentration of the sodium hydroxide solution is 8 to 16 mol / L, and the ratio of the two is 1.1 to 1.4:1.
[0017] Preferably, the silane coupling agent is one of KH-550, KH-560 and KH-570.
[0018] Preferably, the particle size of the calcined coal gangue powder is ≤74 μm, and the calcined coal gangue powder is obtained by calcining coal gangue at 700-800° C. for 2-4 hours.
[0019] Preferably, the melting point of the low-melting-point glass powder is 300-500°C.
[0020] Preferably, the defoaming agent is polydimethylsiloxane.
[0021] The present invention also provides a method for preparing a fire-retardant integrated coating, comprising the following steps:
[0022] (1) ultrasonically stirring the prepared alkaline activator for 5 to 10 minutes and cooling to room temperature to obtain an alkaline activator solution;
[0023] (2) After the fly ash, calcined coal gangue powder, metakaolin and alkaline activator solution are stirred for 5 to 10 minutes, an organic silicone resin, a silane coupling agent and a defoaming agent are added and the stirring is continued for 10 to 15 minutes to obtain an organic modified polymer binder;
[0024] (3) Inorganic filler, flame retardant cosolvent and plasticizer are added to the organic modified polymer binder in sequence, and stirred for 15 to 20 minutes to obtain a fire retardant integrated coating.
[0025] Preferably, the stirring speed in steps (1), (2) and (3) is 400 to 500 rpm / min.
[0026] The beneficial effects of the present invention are:
[0027] The coating matrix of the present invention uses a large amount of geopolymers prepared from coal gangue and fly ash solid waste as raw materials instead of cement or organic glue as a coating binder, which ensures bonding strength while being environmentally friendly. In addition, the coating utilizes the ceramic properties of the geopolymer matrix, and adds a co-solvent therein so that the prepared coating surface can spontaneously form a dense and hard ceramic insulation layer in a high-temperature flame above 300°C, blocking the further diffusion of heat and oxygen, and having good thermal insulation and flame retardant properties. The fire-retardant integrated coating is applied in the field of flame retardancy and fire prevention on the surface of buildings or metal equipment, and has a good protective effect, and can effectively solve the existing cement-based and organic binder fire-retardant coatings. The existing problems such as high energy consumption, environmental pollution, easy aging, and low fire resistance limit. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a diagram showing the surface changes of the coating coated with the fire-retardant integrated coating of the present invention under different temperature conditions. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0030] Example 1
[0031] This embodiment provides a fire-retardant integrated coating and a preparation method thereof.
[0032] (1) A fire-retardant integrated coating, comprising the following components in parts by weight: 223.6 parts of an organic modified polymer binder, 14 parts of an inorganic filler, 38 parts of a flame retardant flux, and 13 parts of a plasticizer;
[0033] in,
[0034] The organic modified geopolymer binder includes 40 parts of fly ash, 20 parts of calcined coal gangue powder, 10 parts of metakaolin; 60 parts of alkali activator, 25 parts of organic silicone resin, 2 parts of KH-550 silane coupling agent, and 0.2 parts of defoaming agent;
[0035] The inorganic filler includes 4 parts of mica powder, 3 parts of zirconium oxide powder and 3 parts of sepiolite powder;
[0036] The flame retardant flux includes 10 parts of low-melting-point glass powder with a melting point of 400°C, 8 parts of zinc borate, and 4 parts of sodium polyphosphate;
[0037] The plasticizer includes 2 parts of modified organic nano-montmorillonite (commercially available), 1 part of brucite and 2 parts of hydrotalcite.
[0038] (2) A method for preparing a fire-retardant integrated coating comprises the following steps:
[0039] S1. Prepare 10 mol / L NaOH solution in a volumetric flask and set it aside after cooling to room temperature; take a sodium silicate water glass solution with a Baume degree of 40Be and a 10 mol / L NaOH solution, the mass ratio of the sodium silicate water glass solution to the sodium hydroxide solution is 1.4:1, stir ultrasonically at 500 rpm / min for 10 minutes under sealed conditions, and then continue to cool at room temperature for 30 hours to obtain an alkali activator for standby use.
[0040] S2. After calcining the coal gangue at 700° C. for 3 hours, the coal gangue is crushed and sieved to obtain calcined coal gangue powder with a particle size of ≤74 μm.
[0041] S3. Evenly mix 10 parts of low-melting-point glass powder with a melting point of 400°C, 8 parts of zinc borate and 4 parts of sodium polyphosphate to obtain a flame retardant solvent; evenly mix 4 parts of mica powder, 3 parts of zirconium oxide powder and 3 parts of sepiolite to obtain an inorganic filler; evenly mix 2 parts of modified organic nano-montmorillonite, 1 part of brucite and 2 parts of hydrotalcite to obtain a plasticizer.
[0042] S4. Prepare an organic modified geopolymer binder: weigh 40 parts of fly ash, 20 parts of calcined coal gangue powder, and 10 parts of metakaolin, stir at 500 r / min for 10 minutes and mix them evenly; then add 60 parts of alkali activator solution, 25 parts of silicone resin, 2 parts of KH-550 silane coupling agent, and 0.2 parts of defoamer respectively to obtain an organic modified geopolymer binder;
[0043] S5. Preparation of environmentally friendly ceramicizable organic-inorganic polymer hybrid geopolymer-based fire-retardant integrated coating: 223.6 parts of organic modified geopolymer binder are taken, stirred at 500r / min for 15 minutes, and then 14 parts of inorganic filler, 38 parts of flame retardant fluxing agent and 13 parts of plasticizer are added in sequence, and finally stirring is continued for 10 minutes to obtain the geopolymer fire-retardant integrated coating.
[0044] Example 2
[0045] This embodiment provides a fire-retardant integrated coating and a preparation method thereof.
[0046] (1) A fire-retardant integrated coating, comprising the following components in parts by weight: 223.6 parts of an organic modified polymer binder, 14 parts of an inorganic filler, 38 parts of a flame retardant flux, and 13 parts of a plasticizer;
[0047] in,
[0048] The organic modified geopolymer binder includes 55 parts of fly ash, 30 parts of calcined coal gangue powder, 20 parts of metakaolin; 80 parts of alkali activator, 35 parts of organic silicone resin, 3 parts of KH-550 silane coupling agent, and 0.6 parts of defoaming agent;
[0049] The inorganic filler includes 5 parts of mica powder, 4 parts of zirconium oxide powder and 5 parts of sepiolite powder;
[0050] The flame retardant flux includes 20 parts of low-melting-point glass powder with a melting point of 400°C, 12 parts of zinc borate, and 6 parts of sodium polyphosphate;
[0051] The plasticizer includes 6 parts of modified organic nano-montmorillonite (commercially available), 3 parts of brucite and 4 parts of hydrotalcite.
[0052] (2) A method for preparing a fire-retardant integrated coating comprises the following steps:
[0053] S1. Prepare 10 mol / L NaOH solution in a volumetric flask and set it aside after cooling to room temperature; take a sodium silicate water glass solution with a Baume degree of 40Be and a 10 mol / L NaOH solution, the mass ratio of the sodium silicate water glass solution to the sodium hydroxide solution is 1.4:1, stir ultrasonically at 500 rpm / min for 10 minutes under sealed conditions, and then continue to cool at room temperature for 30 hours to obtain an alkali activator for standby use.
[0054] S2. After calcining the coal gangue at 700° C. for 3 hours, the coal gangue is crushed and sieved to obtain calcined coal gangue powder with a particle size of ≤74 μm.
[0055] S3. Evenly mix 20 parts of low-melting-point glass powder with a melting point of 400°C, 12 parts of zinc borate, and 6 parts of sodium polyphosphate to obtain a flame retardant solvent; evenly mix 5 parts of mica powder, 34 parts of zirconium oxide powder, and 5 parts of sepiolite to obtain an inorganic filler; evenly mix 6 parts of modified organic nano-montmorillonite, 3 parts of brucite, and 4 parts of hydrotalcite to obtain a plasticizer.
[0056] S4. Prepare an organic modified geopolymer binder: weigh 55 parts of fly ash, 30 parts of calcined coal gangue powder, and 20 parts of metakaolin, stir at 500 r / min for 10 min and mix them evenly; then add 80 parts of alkali activator solution, 35 parts of silicone resin, 3 parts of KH-550 silane coupling agent, and 0.6 parts of defoamer respectively to obtain an organic modified geopolymer binder;
[0057] S5. Preparation of environmentally friendly ceramicizable organic-inorganic polymer hybrid geopolymer-based fire-retardant integrated coating: 223.6 parts of organic modified geopolymer binder are taken, stirred at 500r / min for 15 minutes, and then 14 parts of inorganic filler, 38 parts of flame retardant fluxing agent and 13 parts of plasticizer are added in sequence, and finally stirring is continued for 10 minutes to obtain the geopolymer fire-retardant integrated coating.
[0058] Example 3
[0059] This embodiment provides a fire-retardant integrated coating and a preparation method thereof.
[0060] (1) A fire-retardant integrated coating, comprising the following components in parts by weight: 223.6 parts of an organic modified polymer binder, 14 parts of an inorganic filler, 38 parts of a flame retardant flux, and 13 parts of a plasticizer;
[0061] in,
[0062] The organic modified geopolymer binder includes 70 parts of fly ash, 40 parts of calcined coal gangue powder, 30 parts of metakaolin; 100 parts of alkali activator, 45 parts of organic silicone resin, 4 parts of KH-550 silane coupling agent, and 1 part of defoaming agent;
[0063] The inorganic filler includes 6 parts of mica powder, 5 parts of zirconium oxide powder and 7 parts of sepiolite powder;
[0064] The flame retardant flux includes 30 parts of low-melting-point glass powder with a melting point of 300° C., 16 parts of zinc borate, and 8 parts of sodium polyphosphate;
[0065] The plasticizer includes 10 parts of modified organic nano-montmorillonite (commercially available), 5 parts of brucite and 6 parts of hydrotalcite.
[0066] (2) A method for preparing a fire-retardant integrated coating comprises the following steps:
[0067] S1. Prepare 10 mol / L NaOH solution in a volumetric flask and set it aside after cooling to room temperature; take a sodium silicate water glass solution with a Baume degree of 40Be and a 10 mol / L NaOH solution, the mass ratio of the sodium silicate water glass solution to the sodium hydroxide solution is 1.4:1, stir ultrasonically at 500 rpm / min for 10 minutes under sealed conditions, and then continue to cool at room temperature for 30 hours to obtain an alkali activator for standby use.
[0068] S2. After calcining the coal gangue at 700° C. for 3 hours, the coal gangue is crushed and sieved to obtain calcined coal gangue powder with a particle size of ≤74 μm.
[0069] S3. Evenly mix 30 parts of low-melting-point glass powder with a melting point of 400°C, 16 parts of zinc borate, and 8 parts of sodium polyphosphate to obtain a flame retardant solvent; evenly mix 6 parts of mica powder, 5 parts of zirconia ceramic powder, and 7 parts of sepiolite to obtain an inorganic filler; evenly mix 10 parts of modified organic nano-montmorillonite, 5 parts of brucite, and 6 parts of hydrotalcite to obtain a plasticizer.
[0070] S4. Prepare an organic modified geopolymer binder: weigh 70 parts of fly ash, 40 parts of calcined coal gangue powder, and 30 parts of metakaolin, stir them at 500 r / min for 10 minutes and mix them evenly; then add 100 parts of alkali activator solution, 45 parts of silicone resin, 35 parts of curing agent, 4 parts of KH-550 silane coupling agent, and 1 part of defoaming agent respectively to obtain an organic modified geopolymer binder;
[0071] S5. Preparation of environmentally friendly ceramicizable organic-inorganic polymer hybrid geopolymer-based fire-retardant integrated coating: 223.6 parts of organic modified geopolymer binder are taken, stirred at 500r / min for 15 minutes, and then 14 parts of inorganic filler, 38 parts of flame retardant fluxing agent and 13 parts of plasticizer are added in sequence, and finally stirring is continued for 10 minutes to obtain the geopolymer fire-retardant integrated coating.
[0072] Comparative Example 1: Difference in fire retardant properties of coatings prepared with geopolymer binders that have not been organically modified.
[0073] The difference between this comparative example and Example 2 is that no silicone resin and curing agent are added.
[0074] Comparative Example 2: Difference in fire retardant properties of geopolymer fire retardant coating without adding flame retardant co-solvent.
[0075] The difference between this comparative example and Example 2 is that no flame retardant flux is added.
[0076] Comparative Example 3: Difference in fire retardant properties of fire retardant coating without adding coal gangue solid waste.
[0077] The difference between this comparative example and Example 2 is that the organic modified polymer binder does not contain solid waste coal gangue.
[0078] (2) The raw material ratios of Examples 1-3 and Comparative Examples 1-3 are shown in Table 1. In Table 1, the organic modified polymer binder is 157-290 parts, the inorganic filler is 10-18 parts, the flame retardant flux is 22-54 parts, and the plasticizer is 5-21 parts;
[0079] Table 1. Raw material ratio
[0080]
[0081] Experimental Example 1: Fire resistance and flame retardant properties test of geopolymer fire retardant integrated coating
[0082] Fire retardant performance test: The fire retardant performance of the geopolymer fire retardant coatings of Examples 1 to 3 and Comparative Examples 1 to 3 was subjected to relevant performance tests in accordance with the standard GB / 14907-2018 "Fire Retardant Coatings for Steel Structures".
[0083] Flame retardant performance test: The flame retardant performance of the geopolymer fire retardant coatings of Examples 1 to 3 and Comparative Examples 1 to 3 was tested for flame retardant time according to T / CECSXXX-202X "Technical Specifications for the Application of Fire Retardant Coatings and Flame Retardant Treatment Agents for Wooden Building Structures".
[0084] The fire retardant performance test and flame retardant performance test results of geopolymer fire retardant integrated coating are shown in Table 2.
[0085] Table 2
[0086]
[0087]
[0088] It can be seen from Table 2 that the geopolymer fire-retardant integrated coatings obtained in Examples 1, 2 and 3 have excellent performance, while the comparative coatings that have not been organically modified and the coatings that have not added flame retardant flux have poor fire resistance, flame retardant time and high temperature crack resistance.
[0089] Experimental Example 2:
[0090] The surface changes of the fire-retardant integrated coating prepared in Example 2 under different temperature conditions are shown in the figure below. Figure 1 shown.
[0091] Depend on Figure 1It can be seen that its fire retardant mechanism is as follows: 25℃-300℃: the geopolymer itself has strong heat insulation and oxygen isolation capabilities. At the same time, the evaporation of water in the coating will also absorb a large amount of heat, releasing water vapor to dilute the surrounding oxygen concentration. 300-500℃: the glass powder and flame retardant flux begin to melt, and the quartz particles in the coal gangue work together to fill the cracks, and the ceramic transformation begins. At this time, in addition to the fire retardant effect of the geopolymer itself, the flame retardant begins to play a role. 500-800℃: The ceramic reaction between the low-melting point glass powder and the flame retardant flux is basically completed, and the loose phosphate and borate ceramic insulation layer on the surface is initially formed, and the crack filling is basically completed. 800-1000℃: The intrinsic ceramic transformation and perfection of the geopolymer generates dense high-temperature resistant sodium nepheline and silicate ceramic phases, and a dense ceramic insulation layer is formed on the coating surface.
[0092] Example 4
[0093] This embodiment provides a fire-retardant integrated coating and a preparation method thereof.
[0094] (1) A fire-retardant integrated coating, comprising the following components in parts by weight: 157.2 parts of an organic modified polymer binder, 10 parts of an inorganic filler, 22 parts of a flame retardant flux, and 5 parts of a plasticizer;
[0095] in,
[0096] The organic modified geopolymer binder includes 40 parts of fly ash, 20 parts of calcined coal gangue powder, 10 parts of metakaolin; 60 parts of alkali activator, 25 parts of organic silicon resin, 15 parts of curing agent, 2 parts of KH-560 silane coupling agent, and 2 parts of defoaming agent;
[0097] The inorganic filler includes 4 parts of mica powder, 3 parts of zirconium oxide powder and 3 parts of sepiolite powder;
[0098] The flame retardant flux includes 10 parts of low-melting-point glass powder with a melting point of 300°C, 8 parts of zinc borate, and 4 parts of sodium polyphosphate;
[0099] The plasticizer includes 2 parts of montmorillonite, 1 part of brucite and 2 parts of hydrotalcite.
[0100] (2) A method for preparing a fire-retardant integrated coating comprises the following steps:
[0101] S1. Prepare 8 mol / L NaOH solution in a volumetric flask and set it aside after cooling to room temperature; take a sodium silicate water glass solution with a Baume degree of 40Be and a 10 mol / L NaOH solution, the mass ratio of the sodium silicate water glass solution to the sodium hydroxide solution is 1.1:1, stir ultrasonically at 400 rpm / min for 5 minutes under sealed conditions, and then continue to cool at room temperature for 30 hours to obtain an alkali activator for standby use.
[0102] S2. After calcining the coal gangue at 800° C. for 2 hours, the coal gangue is crushed and sieved to obtain calcined coal gangue powder with a particle size of ≤74 μm.
[0103] S3. Evenly mix 10 parts of low-melting-point glass powder with a melting point of 300°C, 8 parts of zinc borate and 4 parts of sodium polyphosphate to obtain a flame retardant solvent; evenly mix 4 parts of mica powder, 3 parts of zirconia ceramic powder and 3 parts of sepiolite to obtain an inorganic filler; evenly mix 2 parts of organically modified montmorillonite, 1 part of brucite and 2 parts of hydrotalcite to obtain a plasticizer.
[0104] S4, preparing an organic modified geopolymer binder: weighing 40 parts of fly ash, 20 parts of calcined coal gangue powder, and 10 parts of metakaolin, stirring at 400 r / min for 8 minutes and mixing evenly; then adding 60 parts of alkali activator solution, 25 parts of silicone resin, 15 parts of curing agent, 2 parts of KH-560 silane coupling agent, and 2 parts of defoaming agent respectively to obtain an organic modified geopolymer binder;
[0105] S5. Preparation of environmentally friendly ceramicizable organic-inorganic polymer hybrid geopolymer-based fire-retardant integrated coating: Take 157.2 parts of organic modified geopolymer binder, stir at 400r / min for 10 minutes, then add 10 parts of inorganic filler, 22 parts of flame retardant fluxing agent, 5 parts of plasticizer in sequence, and continue stirring for 20 minutes to obtain the geopolymer fire-retardant integrated coating.
[0106] Example 5
[0107] This embodiment provides a fire-retardant integrated coating and a preparation method thereof.
[0108] (1) A fire-retardant integrated coating, comprising the following components in parts by weight: 290 parts of an organic modified polymer binder, 18 parts of an inorganic filler, 54 parts of a flame retardant flux, and 21 parts of a plasticizer;
[0109] in,
[0110] The organic modified geopolymer binder includes 50 parts of fly ash, 30 parts of calcined coal gangue powder, 20 parts of metakaolin; 60 parts of alkali activator, 25 parts of organic silicon resin, 25 parts of curing agent, 3 parts of KH-570 silane coupling agent, and 1.5 parts of defoaming agent;
[0111] The inorganic filler includes 5 parts of mica powder, 4 parts of zirconium oxide powder and 5 parts of sepiolite powder;
[0112] The flame retardant flux includes 10 parts of low-melting-point glass powder with a melting point of 500°C, 8 parts of zinc borate, and 4 parts of sodium polyphosphate;
[0113] The plasticizer comprises 2 parts of modified organic nano-montmorillonite, 1 part of brucite and 2 parts of hydrotalcite.
[0114] (2) A method for preparing a fire-retardant integrated coating comprises the following steps:
[0115] S1. Prepare 16 mol / L NaOH solution in a volumetric flask and set it aside after cooling to room temperature; take a sodium silicate water glass solution with a Baume degree of 40Be and a 10 mol / L NaOH solution, the mass ratio of the sodium silicate water glass solution to the sodium hydroxide solution is 1.3:1, stir ultrasonically at 350 rpm / min for 8 minutes under sealed conditions, and then continue to cool at room temperature for 30 hours to obtain an alkali activator for standby use.
[0116] S2. After calcining the coal gangue at 650°C for 3 hours, the coal gangue powder with a particle size of ≤74 μm is obtained by crushing and sieving.
[0117] S3. Evenly mix 10 parts of low-melting-point glass powder with a melting point of 500°C, 8 parts of zinc borate and 4 parts of sodium polyphosphate to obtain a flame retardant solvent; evenly mix 5 parts of mica powder, 4 parts of zirconium oxide powder and 5 parts of sepiolite to obtain an inorganic filler; evenly mix 2 parts of modified organic nano-montmorillonite, 1 part of brucite and 2 parts of hydrotalcite to obtain a plasticizer.
[0118] S4, preparing an organic modified geopolymer binder: weighing 50 parts of fly ash, 30 parts of calcined coal gangue powder, and 20 parts of metakaolin, stirring at 350 r / min for 10 min and mixing evenly; then adding 60 parts of alkaline activator solution, 25 parts of silicone resin, 3 parts of KH-570 silane coupling agent, and 1.5 parts of defoaming agent respectively to obtain an organic modified geopolymer binder;
[0119] S5. Preparation of environmentally friendly ceramicizable organic-inorganic polymer hybrid geopolymer-based fire-retardant integrated coating: 290 parts of organic modified geopolymer binder are taken, stirred at 350r / min for 20 minutes, and then 18 parts of inorganic filler, 54 parts of flame retardant fluxing agent, and 21 parts of plasticizer are added in sequence, and finally stirring is continued for 18 minutes to obtain the geopolymer fire-retardant integrated coating.
[0120] In summary, the coating matrix uses a large amount of geopolymers prepared from coal gangue and fly ash solid waste as raw materials instead of cement or organic glue as coating binders, which ensures bonding strength while being environmentally friendly. In addition, the coating utilizes the ceramic properties of the geopolymer matrix, and adds a co-solvent to it so that the prepared coating surface can spontaneously form a dense and hard ceramic insulation layer in a high-temperature flame above 300°C, blocking the further diffusion of heat and oxygen, and having good thermal insulation and flame retardant properties. It has a good protective effect when applied to the flame retardant and fireproof field of buildings or metal equipment surfaces, and can effectively solve the existing cement-based and organic binder fire retardant coatings. High energy consumption, environmental pollution, easy aging, low fire resistance and other undesirable problems.
[0121] The specific implementation methods of the invention are described in detail above, but they are only examples, and the invention is not limited to the specific implementation methods described above. For those skilled in the art, any equivalent modification or substitution of the invention is also within the scope of the invention, therefore, the equalization, modification, improvement, etc. made without departing from the spirit and principle of the invention should be included in the scope of the invention.
Claims
1. A fire-retardant integrated coating, characterized in that: The composition comprises the following components by weight: 157-290 parts of organic modified polymer binder, 10-18 parts of inorganic filler, 22-54 parts of flame retardant flux, 5-21 parts of plasticizer; in, The organic modified geopolymer binder comprises 40-70 parts of fly ash, 20-40 parts of calcined coal gangue powder, 10-30 parts of metakaolin; 60-100 parts of alkali activator, 25-45 parts of organic silicone resin, 2-4 parts of silane coupling agent, and 0.2-2 parts of defoaming agent; The inorganic filler includes 4-6 parts of mica powder, 3-5 parts of zirconium oxide powder, and 3-7 parts of sepiolite powder; The flame retardant flux comprises 10-30 parts of low melting point glass powder, 8-16 parts of zinc borate, and 4-8 parts of sodium polyphosphate; The plasticizer comprises 2 to 10 parts of montmorillonite, 1 to 5 parts of brucite and 2 to 6 parts of hydrotalcite.
2. The fire-retardant integrated coating according to claim 1, characterized in that: The alkaline activator comprises a sodium silicate water glass solution and a sodium hydroxide solution in a mass ratio of 1.1-1.4:1, the Baume degree of the sodium silicate water glass solution is 38.5-50Be, the concentration of the sodium hydroxide solution is 8-16 mol / L, and the ratio of the two is 1.1-1.4:
1.
3. The fire-retardant integrated coating according to claim 1, characterized in that: The silane coupling agent is one of KH-550, KH-560 and KH-570.
4. The fire-retardant integrated coating according to claim 1, characterized in that: The particle size of the calcined coal gangue powder is ≤74 μm, and the calcined coal gangue powder is obtained by calcining coal gangue at 700-800° C. for 2-4 hours.
5. The fire-retardant integrated coating according to claim 1, characterized in that: The melting point of the low-melting-point glass powder is 300-500°C.
6. The fire-retardant integrated coating according to claim 1, characterized in that: The defoaming agent is polydimethylsiloxane.
7. A method for preparing the fire-retardant integrated coating according to any one of claims 1 to 6, characterized in that: The steps include: (1) Ultrasonic stirring the prepared alkaline activator for 5 to 10 minutes, cooling to room temperature, and obtaining an alkaline activator solution; (2) After the fly ash, calcined coal gangue powder, metakaolin and alkali activator solution are stirred for 5 to 10 minutes, the organic silicone resin, silane coupling agent and defoaming agent are added and the stirring is continued for 10 to 15 minutes to obtain an organic modified polymer binder; (3) Inorganic filler, flame retardant cosolvent and plasticizer are added to the organic modified polymer binder in sequence and stirred for 15 to 20 minutes to obtain a fire retardant integrated coating.
8. The method for preparing the fire-retardant integrated coating according to claim 7, characterized in that: The stirring speed in steps (1), (2) and (3) is 400-500 rpm / min.
Citation Information
Patent Citations
Geopolymer tunnel fireproof coating and preparation method thereof
CN103232197B
Interior wall fireproof coating based on metakaolin-based geopolymer and preparation process of interior wall fireproof coating
CN117264445A
Inorganic coating based on fly ash geopolymer and preparation method of inorganic coating
CN113511845A
Anti-crack geopolymer-based inorganic powder coating as well as preparation method and application thereof
CN114196242A
Mineral water-based intumescent fireproof coating and preparation method thereof
CN116285672A